2012
DOI: 10.1097/prs.0b013e3182547a45
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Prosthetic Breast Reconstruction Using AlloDerm Including Outcomes of Different Timings of Radiotherapy

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(78 citation statements)
references
References 35 publications
6
71
0
1
Order By: Relevance
“…In the published studies the contracture rate varied between 0-60% (9,12,13,18,(24)(25)(26)(27)(28) and 0-3% for non-irradiated breasts (12,25,26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the published studies the contracture rate varied between 0-60% (9,12,13,18,(24)(25)(26)(27)(28) and 0-3% for non-irradiated breasts (12,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…CC was graded using the conventional Spear-Baker classification for non-irradiated breasts (30). A modified version of this classification in irradiated breasts (26). Grade III and IV CC were determined as clinically significant CC according to the literature.…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the rates of capsular contracture in one of the larger studies comparing capsular contracture rates between 337 acellular dermal matrix (208 breasts) and non-acellular dermal matrix (129 breasts) in breast reconstructions, our rates are slightly lower (3.8% vs. 3.4%) [14]. Of three breasts with grade II capsular contracture, two (66.6%) received radiotherapy which has been possibly associated with an increased rate of capsular contracture, regardless of acellular dermal matrix use [20].…”
Section: Discussionmentioning
confidence: 91%
“…Of the four breasts with grade II capsular contracture, two (50 percent) received radiation therapy, which has been demonstrated to increase the degree of capsular contracture in two-stage reconstructions, regardless of acellular dermal matrix use. 29,30 Whether matrices are efficacious in decreasing capsular contracture in the irradiated field remains to be determined. They have been shown to limit the histologic changes seen around implants after irradiation, and preliminary studies have shown favorable clinical and histologic results.…”
Section: Discussionmentioning
confidence: 99%